Drug-related problems in hypertensive patients: A cross-sectional study from Indonesia - Larasati Arrum Kusumawardani; Retnosari Andrajati; Azizah Nusaibah (Wolters Kluwer Medknow Publications, 2020)
Objective: The treatment of hypertension requires special attention because of comorbidities and polypharmacy. In a previous study, polypharmacy has been associated with a high risk of drug-related problems (DRPs). This study aimed to analyze DRPs in Indonesian hypertensive patients focusing on drug therapy effectiveness and adverse drug reactions. Methods: A cross-sectional study was conducted using medical records' data, prescriptions, and nursing records to observe DRPs that occurred in outpatients with hypertension from February to April 2019. A total of 114 outpatients aged ≥23 years with a primary diagnosis of primary hypertension were included in this study. DRPs were reviewed based on literature, recent guidelines, and drug interaction software. Classification DRPs were done using Indonesian-translated Pharmaceutical Care Network Europe V6.02. The data obtained were analyzed using univariate descriptive analysis. Findings: Of all participants, 65 (57%) outpatients were found to have DRPs related to treatment effectiveness (54 cases) and adverse drug reactions (36 cases). The primary cause of the problems was an inappropriate drug (94.14%) and dose selection (2.86%). Potential drug interactions were found high (62.14%) in the combination of an antihypertensive agent with other drugs among patients. Overprescribing drugs without clear indications, untreated indications, and subtherapeutic dosage were also reported in this study. Conclusion: A significant percentage of outpatients being treated for hypertension experienced DRPs. The role of clinical pharmacists and physicians in monitoring drug therapy needs to be prioritized to prevent and resolve DRPs in outpatients with hypertension.